Using single-isomer octa(6-O-sulfo)-γ-cyclodextrin for fast capillary zone electrophoretic enantioseparation of pindolol: Determination of complexation constants, software-assisted optimization, and method validation - Kanizsová, Lívia; Ansorge, Martin; Zusková, Iva; Dubský, Pavel (Journal of chromatography. A, 2018)
The present study describes a rapid and effective capillary electrophoresis (CE) method for the enantioseparation of pindolol using single-isomer octa(6-O-sulfo)-γ-cyclodextrin. The complexation parameters were determined under neutral and high pH conditions to identify optimal separation conditions using a theoretical model. Baseline separation of pindolol enantiomers was achieved within 6 min in a sodium/MOPS buffer, pH 7.2, with a selector concentration of 6 mM. The method was validated according to the ICH guidelines using imidazole as an internal standard. Low limits of detection and quantification were found, specifically 1.2 μg/mL and 4 μg/mL (0.6 μg/mL and 2 μg/mL per enantiomer), respectively. The calibration curves showed good linearity, with a coefficient of determination R2 ≥ 0.999 over a 5 - 55 μg/mL concentration range and over a 50 - 300 μg/mL concentration range of the racemic mixture. The relative standard deviations (%RSD) of intra-day and inter-day precision were lower than 8% at LOQ level, lower than 3% at 50 μg/mL level and lower than 1.5% at 300 μg/mL level. Accuracy ranged from 95 to 103% (106% at LOQ level). The proposed method was successfully tested on a medical formulation of Visken® Sandoz intravenous solution and Visken® Teofarma pills for oral use.
Keywords: Software; Limit of Detection; software; stereoizomerie; limita detekce; pufry; Pindolol; Electrophoresis, Capillary; gamma-Cyclodextrins; Method validation; Single-isomer cyclodextrin; Enantioseparation; Stereoisomerism; pindolol; elektroforéza kapilární; reprodukovatelnost výsledků; časové faktory; Capillary electrophoresis; gama-cyklodextriny; Reproducibility of Results; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; Time Factors; kalibrace; β-blockers; Calibration; Buffers